Endovascular revascularisation versus surgical revascularisation in patients with lower limb atherosclerosis obliterans: a protocol for systematic review and meta-analysis with trial sequential analysis and meta-regression - Peng Qiu; Qun Huang; Hongxin Shu; Chuanfei Zeng; Xiaowei Xiong; Xinwu Lu (BMJ Open, 2022)
Introduction The revascularisation strategy for lower limb atherosclerosis obliterans (ASO) remains controversial. In this meta-analysis, we will summarise existing evidence to compare the long-term and short-term outcomes between endovascular revascularisation and open revascularisation for patients with ASO.Methods Relevant randomised controlled trials (RCTs) and cohort studies are included from the following databases: MEDLINE/PubMed, Embase and the Cochrane Library. The last search time is 1 August 2022. Two reviewers will independently identify RCTs and cohort studies according to eligibility and exclusion criteria. The risk of bias of included cohort studies, and RCTs are assessed with the Newcastle-Ottawa Scale, Methodological Index of Non-randomized Studies and Cochrane Collaboration’s tool, respectively. The primary outcomes include overall survival, amputation-free survival and 30-day mortality. TSA Beta Software V.0.9.5.10 is used to perform the trial sequential analysis for primary outcomes. The Grades of Recommendations, Assessment, Development and Evaluation (GRADE) tool will be used to assess the level of evidence for outcome from RCTs. Stata V.17.0 software is used to pool primary outcomes.Ethics and dissemination This study will be disseminated through peer-reviewed journals or conference reports. No ethical approval requirements are required because the results presented in this study are conducted based on published data.PROSPERO registration number CRD42022359591